Current stress field and its relationship to tectonism in a coal mining district, central China, for underground coal energy exploration. (November 2022) - Li, Peng; Cai, Meifeng; Guo, Qifeng; Ren, Fenhua; Miao, Shengjun
Abstract: Adopting 47 sets of in situ stress measurements taken at depths ranging from 417 to 1123 m in a coal mining district in central China by the overcoring method, we characterize the magnitude and orientation of the current stress field and its relationship to tectonism in this district to determine the controls on in situ stress in underground coal energy exploration and seismogeology. The measurements reveal that this district is in a relatively high horizontal stress environment. The stress regimes are generally favorable for strike-slip faulting and reverse faulting and are characterized by σ H > σ v > σ h and σ H > σ h > σ v, revealing that the regional stress field is absolutely dominated by horizontal tectonic stress and reflects a typical tectonic stress field type. The maximum horizontal principal stress is predominantly oriented between the ENE–WSW and WNW–ESE directions and averages nearly E–W, ​ which is closely related to the tectonic plate movement and crustal deformation and agrees well with the direction derived from focal mechanism solutions and other stress indicators in and around the region. The current stress field in this district generally inherited the characteristics of the tectonic stress field in the third stage and partially retained the traces generated by the tectonic stress field in the first and second stages. In addition, the frictional parameter μ m, which is calculated using the derived stress data, is used as a strong predictor to reflect the capability of the level of crustal stress accumulation. This region is in a state of critical or subcritical equilibrium, and regional faults at shallow depths have a medium to slightly high frictional strength, indicating that some well-oriented faults may theoretically approach or reach frictional equilibrium and that frictional sliding may occur. Highlights: The σ H direction in the mining district is dominantly oriented between the ENE–WSW and WNW–ESE or nearly E-W directions. The current stress field in the area generally inherited the characteristics of the tectonic stress field in the third stage. Under the current overall state of stress, the mining district is in a state of critical or subcritical equilibrium.